2009
DOI: 10.1016/j.nima.2009.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Design of a compact high-power neutron source—The EURISOL converter target

Abstract: a b s t r a c tThe EURISOL project, a multi-lateral initiative supported by the EU, aims to develop a facility to achieve high yields of isotopes in radioactive beams and extend the variety of these isotopes towards more exotic types.The neutron source at the heart of the projected facility is designed to generate isotopes by fissioning uranium carbide (UC) targets arranged around a 4 MW neutron source. For reasons of efficiency, it is essential that the neutron source be as compact as possible, to avoid losin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The magnitude of the base frequency is at least a factor of two below the calculated value, approximately 60 Hz, depending on assumptions [6]. It would therefore appear that the support afforded to the target by the test rig is not as stiff as expected.…”
Section: Rž Milenković Et Al / Nuclear Instruments and Methods In mentioning
confidence: 77%
See 2 more Smart Citations
“…The magnitude of the base frequency is at least a factor of two below the calculated value, approximately 60 Hz, depending on assumptions [6]. It would therefore appear that the support afforded to the target by the test rig is not as stiff as expected.…”
Section: Rž Milenković Et Al / Nuclear Instruments and Methods In mentioning
confidence: 77%
“…This was expected as a prior dynamic analysis by Samec et al [6] pressure variations from a CFD analysis to a structural FEM model indicated that resonance in the vanes was likely to lead to high cycle fatigue at 200 Hz and failure after a few hours of operation due to a weakness in the design of the flow vanes. Thus any further increase of the flow rate and decrease of the operating pressure, in particular a prolonged operation under critical conditions, are likely to lead to a failure of the flow vanes and/or the welds that hold them.…”
Section: Rž Milenković Et Al / Nuclear Instruments and Methods In mentioning
confidence: 80%
See 1 more Smart Citation
“…Computational Fluid Dynamics (CFD) tools are commonly used for the thermal and hydraulic design of facilities operating with liquidmetal, e.g., MYRRHA [17], ESS [18] and EURISOL [8,19]. Furthermore, important aspects of CFD analysis such as the turbulence modeling, pressure field and pressure drop in a liquid-metal flow have been validated in the framework of thermal-hydraulics design of the MEGAPIE LBE target [8,19].…”
Section: Methodsmentioning
confidence: 99%
“…Concerns for the design of these targets include effects like pressure drop, cavitation, liquid-metal recirculation, instabilities, non-uniform flows etc. [7][8][9]. Studies conducted in the past by different researchers highlight the importance of these effects on the target system [10,11].…”
Section: Introductionmentioning
confidence: 99%